Technological Features of the Production of Granulated Simple Superphosphate According to the Flow Scheme - Xusan Otaboev, Ruzimat Radjabov, Doniyor Sherkuziev, Shafoat Namazov, Atanazar Seytnazarov (International Journal of Advanced Science and Technology, 2020)
The classic method of simple ammoniated superphosphate includes: decomposition of phosphate raw materials in sulfuric acid with a concentration of at least 63-68 %, at its norm of 100 % stoichiometry and at a temperature of 70-75 °C. Chamber maturation of superphosphate mass for 1-1,5 hours at a temperature of 115-120 °C; storage ripening for 6 days with 3 times stirring; granulation and ammonization (humidity of superphosphate before granulation 14-15 %); drying and sieving of the product.